Higher Controlling Nutritional Status (CONUT) score indicates increased risk of sarcopenia in elderly hospitalized patients: a single institution study in China - Sun, Leying; Yang, Yilin; Yan, Ruiyi; Xu, Bingqing; Zhang, Kaiyu; Zhu, Wenyu; Lian, Xiaoyi; Xu, Yihui; Liu, Lei; Gao, Xiuming; Guo, Zhengli; Zhou, Mingqin (Frontiers in Nutrition, 2025)
BackgroundThe Controlled Nutritional Status (CONUT) metric has demonstrated effectiveness as a prognostic indicator for acute and chronic diseases in addition to other wasting conditions. However, its association with sarcopenia in elderly hospitalized patients remains insufficiently explored. Our study objectives included the assessment of the potential of CONUT score to predict sarcopenia onset.MethodsOur study was a single center retrospective cohort study. Patients from the Department of Geriatrics of the First People’s Hospital of Kunshan were recruited for this study. Multiple indicators related to nutrition and sarcopenia, including CONUT, Prognostic Nutritional Index (PNI), triglyceride–total cholesterol–body weight index (TCBI), Geriatric Nutritional Risk Index (GNRI), and handgrip strength (HGS). Spearman’s and Pearson’s correlation were calculated to assess the associations between nutritional indices and sarcopenia-related indicators. The demographic characteristics, physical examination findings and laboratory parameters were included in univariate logistic regression. Based on the results of univariate logistic regression and theoretical analysis, variables were selected for multivariate logistic regression in order to identify risk factors for sarcopenia.ResultsA total of 236 elderly hospitalized patients were included. Malnutrition was prevalent in patients with sarcopenia. The optimal CONUT cut-off values were defined as >4 for males and >3 for females, dividing patients into high CONUT (n = 140, 59.32%) and low CONUT (n = 96, 40.58%) groups. Patients in the high CONUT group had lower levels of albumin, prealbumin, hemoglobin, and total lymphocyte count. Multivariate logistic regression analysis showed that a high CONUT score was an independent risk factor for sarcopenia (OR:1.814, 95% CI: 1.019–3.255, p = 0.044). Male sex and low iron level were also demonstrated to be associated with sarcopenia.ConclusionCONUT score is an independent risk factor for sarcopenia and may serve as a practical indicator for sarcopenia risk screening in elderly hospitalized patients.